Facile synthesis of coumaronochromones through palladium-catalyzed intramolecular cross dehydrogenative coupling. (9th April 2021) - Gu, Chang-Xue; Liu, Jian-Guo; Chen, Wen-Wen; Xu, Ming-Hua
Abstract: An efficient base-free palladium-catalyzed intramolecular cross dehydrogenative coupling of 2-aryloxy substituted 4-chromenones to access coumaronochromones has been achieved. A range of diversely substituted coumaronochromones can be facilely synthesized in good to excellent yields (up to 90%). Graphical abstract: To create your abstract, type over the instructions in the template box below. Fonts or abstract dimensions should not be changed or altered. Leave this area blank for abstract info. Image 1